Transitions from Charismatic Rule: Theories of Leadership Change and Cuba's Post-Fidel Succession - Bert Hoffmann (German Institute of Global and Area Studies (GIGA), 2007)
For theories of political succession and charismatic authority, the almost half-century long rule of Fidel Castro presents an extraordinary test case since Fidel in July 2006 handed over power 'temporarily' to his deputy and brother Raúl. On the background of Max Weber's work on charismatic rule, the paper analyzes the way in which the Cuban leadership has responded to the succession question and identifies four aspects in which it differs from the succession problems typically attributed to charismatic rule: Cuba's longstanding exceptionalism regarding the 'second man' behind the leader; the succession during the life-time of the leader with a sui generis modus of 'cohabitation' between the outgoing and the incoming leader; the routinization of charisma which domestically allows a bureaucratic succession model with the Communist Party, rather than any individual, being postulated as Fidel Castro's heir; and as a correlate to the latter, the ritual transmission of Fidel's charisma to a heir beyond the nation-state, Venezuela's Hugo Chávez, as the new charismatic leader to continue Fidel Castro's universal revolutionary mission. – – Für Theorien politischer Nachfolge und charismatischer Herrschaft stellt die fast ein halbes Jahrhundert währende Herrschaft Fidel Castros in Kuba einen denkbar prominenten Testfall dar, seit Fidel Castro im Juli 2006 die Amtsgeschäfte 'vorübergehend' an seinen Vize und Bruder Raúl übergab. Max Webers Werk über charismatische Herrschaft aufgreifend, analysiert der vorliegende Artikel, wie die kubanische Führung auf die Nachfolgefrage geantwortet hat und identifiziert dabei vier Aspekte, die den kubanischen Fall von den typischerweise charismatischer Herrschaft zugeschriebenen Nachfolgeproblemen unterscheiden: Die Ausnahmerolle in Bezug auf den 'zweiten Mann' hinter der Führungsperson; die Amtsnachfolge zu Lebzeiten mit einem ungewöhnlichen Modus der 'Cohabitation' zwischen scheidendem Führer und designiertem Nachfolger; die Routinisierung des Charismas, die auf nationaler Ebene ein bürokratisches Nachfolgemodell ermöglicht, bei dem die Kommunistische Partei an Stelle eines individuellen Politikers das Erbe Fidels antritt; und schließlich, als Korrelat des vorangehenden, die rituelle Übertragung des Charismas Fidels zu einem Erben jenseits der nationalen Grenzen in Gestalt des venezolanischen Präsidenten Hugo Chávez, der als neuer charismatischer Führer zum Träger der universellen Revolutionsmission Fidel Castros erhoben wird.
Keywords: 300; political succession; leadership change; charismatic authority; Max Weber; Cuba